(3/x)-1 = 7/(x-20)
Looks nasty, I agree, but it's not as bad as it looks!
Multiply across by x(x-20) and you are left with
(3-x)(x-20) = 7x
which expands out into a neat quadratic with two friendly numbers as your solutions.
i tried and tried and i cant find the answer. is it not a solution.
(3/x)-1=7/(x-20)
2 answers
ahhh, I thought so the last time you posted that question.
so this time we multiply each term by x(x-2) to get
3(x-20 - x(x-20) = 7x
3x - 60 - x^2 + 20x = 7x
x^2 -16x + 60 = 0
(x-10)(x-6) = 0
x = 10 or x = 6
so this time we multiply each term by x(x-2) to get
3(x-20 - x(x-20) = 7x
3x - 60 - x^2 + 20x = 7x
x^2 -16x + 60 = 0
(x-10)(x-6) = 0
x = 10 or x = 6